Strategi Pemasaran Jemput Bola dalam Meningkatkan Minat Nasabah Terhadap Tabungan - Faisol, Mokhamad; Wahyudi, M Ilham (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2023)
The sharia financial system is a financial system that bridges parties who need funds and parties who have excess funds through financial products and services that comply with sharia principles. To increase market share, the products offered must have a marketing strategy so that they can be seen. The bank marketing concept is actually not much different from the marketing concept for other business sectors, such as the manufacturing industry sector, service business sector and others. Therefore, we want to conduct research with the title Pick-up Marketing Strategy to Increase Customer Interest in Savings (BMT Maslahah Gondangwetan). With the aim of finding out the strategy used by BMT to increase customers using descriptive qualitative research methodology. The results of the research are that customers and agencies are targeted in carrying out a pick-up strategy, because most of the Gondangwetan area work as traders who need funds to develop their business.